Knowledge, attitudes, practices and behaviors regarding deceased organ donation and transplantation in Malaysia's multi-ethnic society: a baseline study - Wong, L.P. (2011)
Background: Malaysia's organ and tissue donation rates are among the lowest in the world. The study aims to explore the knowledge, attitudes, practices and behaviors regarding deceased organ donation and transplantation in the diverse ethnic communities in the state of Selangor, Malaysia. Methods: A cross-sectional, population-based, computer-assisted telephone interview exploring multi-ethnic participants' knowledge, attitudes, practices and behavioral on deceased organ donation and transplantation was conducted from February to April 2009. Results: Although only 5.5 of the total participants (N = 1174) reported that they have registered to be organ donor, a further 35.2 of those who have not register for organ donation indicated willingness to donate their own. Significant socio-demographic disparities with respect to knowledge and attitudes scores were observed. In particular, Malays (20.7) indicated lower willingness to donate organs compared to the Chinese (36.6) and Indians (51.4) (p < 0.001). In multivariate logistic regression analysis, willingness to donate one's own organ was associated with knowledge score (odds ratio OR = 1.17, 95% confidence interval CI = 1.13-1.22), attitude score (OR = 1.17, 95% CI = 1.05-1.31), secondary school education (OR = 1.46, 95% CI = 1.05-2.02), and Malay ethnicity (OR = 0.18, 95% CI = 0.03-0.94). Conclusion: Findings assist organ donation and transplantation organizations to reach out the diverse socio-demographic and ethnic communities with cultural-specific information about organ donation.